SIFAT KELENGKAPAN DAN KEKOMPAKAN PADA RUANG METRIK HAUSDORFF - Dewanti Inesia Putri; Arta Ekayanti (Universitas Muhammadiyah Ponorogo, 2019)
In this paper, will be discuss the definition of the Hausdorff metric space, completeness of the Hausdorff metric space, and compactness of the Hausdorff metric space. By used the theory of the metric space, the compact set was given the definition of the Hausdorff metric space. By used the completeness of the metric space, it is shown that the Hausdorff metric space was complete if the metric space was complete. Furthermore, used the compactness of the metric space was shown the Hausdorff metric space was compact if the metric space was compact